A novel method for the activity measurement of large-area beta reference sources. (March 2016) - Stanga, D.; De Felice, P.; Keightley, J.; Capogni, M.; Ioan, M.R.
Abstract: A novel method has been developed for the activity measurement of large-area beta reference sources. It makes use of two emission rate measurements and is based on the weak dependence between the source activity and the activity distribution for a given value of transmission coefficient. The method was checked experimentally by measuring the activity of two ( 60 Co and 137 Cs) large-area reference sources constructed from anodized aluminum foils. Measurement results were compared with the activity values measured by gamma spectrometry. For each source, they agree within one standard uncertainty and also agree within the same limits with the certified values of the source activity. Highlights: A novel method for determining the activity of large-area sources is described. The method makes use of two emission rate measurements. It has uncertainties smaller than the limit of 10% required by ISO 8769.